Chondrosarcoma secondary to hereditary multiple exostosis treated by extended internal hemiplevectomy - Lopes, Ademar (1997)
The authors report on the case of a 28-year-old patient with extensive chondrosarcoma of the left ischium and pubis involving hip joint, skin, and soft tissue of the gluteal region, secondary to hereditary multiple exostosis submitted to an extended internal Enneking type II and Ill hemipelvectomy. No prosthesis or arthrodesis was used. A few years ago, patients with extensive tumors like this one were treated with interilioabdominal amputation, resulting in a loss of quality of Iife.Two years after the limb-preserving surgery, this patient was disease free, with good functional results, including bipedal ambulation with support.